2001
DOI: 10.1124/mol.60.1.217
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits Phorbol Ester and UV-Induced Activator Protein 1 Activation by Interfering with Mitogen-Activated Protein Kinase Pathways

Abstract: Resveratrol, a phenolic compound found in grapes and other food products, prevents chemical-induced carcinogenesis in a number of animal models of cancers. To better understand its chemopreventive property, we examined effects of resveratrol on the activity of activator protein 1 (AP-1), a dimeric transcription factor that plays a critical role in the carcinogenesis and tumor transformation. Pretreatment of HeLa cells with resveratrol inhibited the transcription of AP-1 reporter gene by UVC and phorbol 12-myri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(78 citation statements)
references
References 31 publications
6
72
0
Order By: Relevance
“…27,56 For example, the natural product Resveratrol inhibits AP-1 and NFκB activity and the subsequent activation of their target genes. [57][58][59][60] We have shown that the HIV-1 induced changes in DNMT1 expression 22,30 (Fig. 1) are most likely mediated through the transcription factor AP-1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…27,56 For example, the natural product Resveratrol inhibits AP-1 and NFκB activity and the subsequent activation of their target genes. [57][58][59][60] We have shown that the HIV-1 induced changes in DNMT1 expression 22,30 (Fig. 1) are most likely mediated through the transcription factor AP-1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Besides inhibiting the catalytic activity of COX-2, the compound also blocks TPA-mediated induction of COX-2 mRNA in cultured human mammary epithelial cells through repression of AP-1-dependent transactivation [108]. It also inhibits AP-1-, ERK1-, and protein kinase C (PKC)-mediated induction of COX-2 promoter activity [128]. A recent study demonstrated that topically applied resveratrol inhibits TPA-induced COX-2 expression in female ICR mouse skin, further supporting its antitumor-promoting potential [55].…”
Section: Resveratrolmentioning
confidence: 99%
“…26 In most cancer cell lines, AP-1 is highly activated, and polyphenols (theaflavin, EGCG, and resveratrol) were described to inhibit the transcriptional activity of AP-1 by TNF-a, PMA, and UV radiation. [27][28][29] In addition, the mechanism behind this decreased activity seems to be the blockade of the ERK2, JNK-1, and p38 MAPK activation, 27 which are the upstream kinases that regulate activation of both NF-kB and AP-1. 24 …”
Section: B Suppression Of Ap-1 Transcription Factor Activationmentioning
confidence: 99%